Cultural Identity and Aesthetics in Indian Folk Dance Thidambu Nritham: A Performance Outlook - Puthumana, Govindan Namboothiri; Puthumana, Govindan (International Journal of Culture and Art Studies, 2021)
Thidambu Nritham is an ancient Indian folk dance performed in villages of North Malabar in Kerala state. The performance follows several rules of Natya shastra, and at the same time, has influenced the cultural and social life of Malabar due to the ritualistic nature. According to the background and history, Kolathiri dynasty has introduced Thidambu Nritham as a part of temple rituals, the art form being seven-century old. Thidambu Nritham is deep-rooted in the civilization of north Kerala, as it has close links with agrarian culture and harvests in the region. The elements used for rituals and ceremonies in Thidambu Nritham connect with soil fertility and prayers for an enhanced crop yield. The aesthetics of Thidambu Nritham is related to the colourful decorations of thidambu using flowers and drumming in four rhythms. The culture of temple procession and worshippers joining the celebration could be traced from the prehistoric Indian tradition and heritage.